Bismuth-Containing Alloys and Nanostructures - Wang, Shumin; Lu, Pengfei; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book focuses on novel bismuth-containing alloys and nanostructures, covering a wide range of materials from semiconductors, topological insulators, silica optical fibers and to multiferroic materials. It provides a timely overview of bismuth alloys and nanostructures, from material synthesis and physical properties to device applications and also includes the latest research findings. Bismuth is considered to be a sustainable and environmentally friendly element, and has received increasing attention in a variety of innovative research areas in recent years. The book is intended as a reference resource and textbook for graduate students and researchers working in these fields. .
Theoretical simulations of dilute bismides -- Epitaxial growth of dilute bismides -- III-As-Bi alloys -- III-P-Bi, III-Sb-Bi and other III-Bi alloys -- Influence of bismuth on nanostructures -- Surface and structural properties, surfactant effect -- Electric, transport and optical properties -- Device applications of dilute bismides -- Bismuth-containing 2D materials -- Epitaxial growth of Bi2X3 (X=Se and Te) -- Thermoelectric properties of Bi2X3 (X=Se and Te) -- Bi2X3 (X=Se and Te) as topological insulators -- Dilute bismuth optical fibers -- Bismuth containing superconductors.
Keywords: Optical materials; Nanotechnology; Microtechnology; Microelectromechanical systems; Semiconductors; Nanochemistry; Nanoscience; Optical Materials; Nanotechnology; Microsystems and MEMS; Semiconductors; Nanochemistry; Nanophysics